Espacio, territorio y la política del agua en las sierras chicas de Córdoba - Argentina / Space, territory and the politics of water in Sierras Chicas - Córdoba - Argentina - Adrian Koberwein (Sociedade & Natureza)
A diversity of initiatives carried out by groups and institutions to find solutions to the water crisis affecting the area of ‘Sierras Chicas’ in the Province of Córdoba, Argentina, are articulated with certain space-territorial dynamics. In this article, and based on an ethnographic and comparative analysis, I describe and analyze different conflicts about the appropriation of water resources. These conflicts can only be explained in relation to their spatial and territorial dimension. I understand space-territory in terms of its social production; that is, in terms of change and transformation that are product of human activity. To understand space-territory in processual and relational terms, specifically in relation to the appropriation of water resources, I propose that we must also attend the relatively permanent and fixed forms that it adopts, and understand the specific ways in which the dynamics of appropriation and control of natural resources such as water, are articulated with different forms of space-territory production.